Elektroniczne usługi publiczne : zarys problemów dotyczących kadr i edukacji informatycznej w administracji publicznej - Kowalczyk, Lucjan (Public e-Services : Some Problems Concerning Workers and their IT Education in Public Administration - Outline, 2007)
With regard to low intenzity of utilizing IT technologies and systems in the public sector (and public services in particular) in Poland as compared with other EU member states, the paper presents: theoretical context, including the concept of information society in relation to the public sector and public services, some IT systems meeting the relevant legal criteria and suitable for implementation in the public sector, the role of public sector workers and their education in the process of transformations related to the implementation and practical use of IT technologies and systems in public services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1161, s. 600-612